Effect of non-identity of beam position monitors manufacturing on measurement accuracy of the reference orbit coordinates - Ivashchenko, V.E.; Karnaukhov, I.M.; Trotsenko, V.I.; Shcherbakov, A.A. (Вопросы атомной науки и техники, 2007)
Effect of geometrical and electrical non-identity of monitors manufacturing on accuracy of measurement of beam position has been studied. It has been shown, that even providing mechanical accuracy of monitor manufacturing of about ±100µm and deviation of electric capacity of electrodes equal to ±2%, their operating characteristics near the monitor center may differ from each other more than on ±300µm.